Effects of Food Insecurity and Psychosocial Health Challenges on Students’ Academic Performance in Federal College of Education, Zaria, Nigeria - ZAKARI, Safiyanu Bello; ABDULLAHI, Hadiza (Ilorin Journal of Education, 2023)
This study assessed food insecurity and psychosocial health challenges and its associated effects on the Academic Performance among student of Federal College of Education, Zaria. The study employs survey design. The target population comprises three hundred and eleven (311) respondents were selected using a purposive sampling technique from each of the eight (8) departments in the school. A well-constructed questionnaire was used to obtain the data. We analyzed the data using both descriptive and logistic regression analysis. Research shows that students with low GPA have the highest rates of academic performance problems due to food insecurity Students with food insecurity are more likely to experience anxiety, which affects their academic performance The more students are at risk of depression because of food insecurity, the lower their academic performance is. Among other things, the study recommends that: Students should receive guidance from school authority on how to consume nutritious and quality foods properly to reduce the negative effects of food insecurity. Institutions of higher learning developed an established virtual academic, social, and mental health support services for students and thought about modifying student support services to broaden outreach to the requirements of food-insecure students. The institution could collaborate with a local non-profit organization that provides food supplies, to mention a few things, to help the on-campus students who are struggling with food insecurity.